Unmet need for family planning in Ethiopia and its association with occupational status of women and discussion to her partner: a systematic review and meta-analysis - Solomon Adanew Worku; Yohannes Moges Mittiku; Abate Dargie Wubetu (BMC, 2020)
Abstract Background Unmet need refers to fecund women who either wish to postpone the next birth (spacers) or who wish to stop childbearing (limiters) but are not using a contraceptive method. Many women who are sexually active would prefer to avoid becoming pregnant but are not using any method of contraception. These women are considered to have an unmet need for family planning. Therefore, the objective of this systematic review and meta-analysis is to estimate the pooled prevalence of unmet need for family planning and its association to occupational status of women and discussion to her partner among fecund women in Ethiopia. Method A systemic review and meta-analysis was conducted using published and unpublished research on the prevalence of unmet need for family planning and its association to occupational status of women and discussion to her partner among fecund women in Ethiopia. Data extraction was designed in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Studies were accessed through electronic web-based search from PubMed, Cochrane Library, Google Scholar, CINAHL, and Embase. All statistical analysis were done using STATA version 14 software using random effects model. The pooled prevalence was presented in forest plots. Results A total of 9 studies with 9785 participants were included, and the overall pooled estimated prevalence of unmet need for family planning among fecund women in Ethiopia was 34.90% (95% CI: 24.52, 45.28%). According to subgroup analysis the estimated prevalence of unmet need for family planning in studies conducted in Amhara was 32.98% (95% CI: 21.70, 44.26%), and among married women was 32.84% (95% CI: 16.62, 49.07%). Additionally, housewife women were 1.6 times more likely have unmet need for family planning compared to government employed women (OR: 1.6, 95% CI: 1.29, 1.99). Moreover, women who don't discuss to partner were 1.87 times more likely to have unmet need for family planning compared to women who had discussion to her partner (OR 1.87; 95% CI: 1.52, 2.31). Conclusion The analysis revealed that the overall prevalence of unmet need for family planning among fecund women in Ethiopia was high. Family planning programs should identify strategies to improve communication in family planning among couples and to ensure better cooperation between partners.